Perbandingan Skor Basil Tahan Asam Pewarnaan Ziehl Neelsen dan Ziehl Neelsen Bleach 2% Spesimen Sputum pada Penderita Tuberkulosis Paru di Rumah Sakit Santa Elisabeth Medan - Halawa, Felisitas Putri Abadi; Bangun, Seri Rayani; Taringan, Rica Vera Br (Universitas Malahayati, 2023)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. One way to diagnose this disease is by microscopic examination using the Ziehl Neelsen method. Bleach is a decontaminant solution that can help reduce microscopic dirt and sterilize microscopic fields of view. This study aims to determine the comparison of Ziehl Neelsen staining acid fast bacilli scores and Ziehl Neelsen Bleach 2% sputum specimens in patients with pulmonary tuberculosis. The design used is pre-experimental with 36 sputum samples taken. Data analysis is performed by bivariate analysis using the Wilcoxon test at value of 0.05. From this study, the results for Ziehl Neelsen staining are 30.6% negative, 11.1% scanty, 19.4% positive 1 (+1), 16.7% positive 2 (+2), 22.2% positive 3 (+3), while for Ziehl Neelsen staining Bleach 2% as much as 25% negative, 16.7% scanty, 19.4% positive 1 (+1), 16.7% positive 2 (+2), 22.2% positive 3 (+3). The results of bivariate analysis show a p value of 0.157 so it is concluded that there is no difference in the positivity rate of microscopic TB smear results between the addition of 2% bleach solution compared to ordinary Ziehl Neelsen staining. Keywords: Mycobacterium Tuberculosis, Staining of Acid-Fast Bacilli (AFB), Ziehl-Neelsen, Bleach. ABSTRAK Tuberkulosis (TB) adalah penyakit menular yang disebabkan oleh Mycobacterium tuberculosis. Salah satu cara untuk mendiagnosis penyakit ini yaitu dengan pemeriksaan mikroskopis metode Ziehl-Neelsen. Bleach merupakan larutan dekontaminan yang dapat membantu mengurangi kotoran mikroskopis dan mensterilkan lapang pandang mikroskopis. Penelitian ini bertujuan untuk mengetahui perbandingan skor basil tahan asam pewarnaan Ziehl Neelsen dan Ziehl Neelsen Bleach 2% spesimen sputum pada penderita Tuberkulosis paru.Desain yang digunakan yaitu pre-eksperimen dengan 36 sampel sputum yang diambil dari pasien TB di Rumah Sakit Santa Elisabeth Medan. Analisis data dilakukan dengan analisis bivariat menggunakan uji Wilcoxon pada nilai α 0,05. Dari penelitian ini didapatkan hasil pada pewarnaan Ziehl Neelsen sebanyak 30.6% negatif, 11.1% scanty, 19.4% positif 1 (+1), 16.7% positif 2 (+2), 22.2% positif 3 (+3), sedangkan pada pewarnaan Ziehl Neelsen Bleach 2% sebanyak 25% negatif, 16.7% scanty, 19.4% positif 1 (+1), 16.7% positif 2 (+2), 22.2% positif 3 (+3). Hasil analisis bivariat menunjukkan nilai p 0.157 sehingga disimpulkan bahwa tidak terdapat perbedaan tingkat kepositifan hasil BTA diagnostik mikroskopik TB antara penambahan larutan bleach 2% dibandingkan dengan pewarnaan BTA Ziehl Neelsen biasa. Kata kunci: Mycobacterium Tuberculosis, Pewarnaan Basil Tahan Asam (BTA), Ziehl- Neelsen, Bleach.